(untitled) (UUM Journal of Legal Studies, 2023)
The positive acceptance of cryptocurrency by the public indicates their interest and enthusiasm for cryptocurrency. Nevertheless, the regulatory overlay related to cryptocurrency is still at its infancy level, posing challenges to its estate administration upon the death of the owner of a cryptocurrency, which will lead to its disappearance and loss as it becomes impossible to be inherited. Hence, in light of this undesirable possibility, this paper aims to analyze the legal and Shariah issues on the estate administration of cryptocurrency from the perspectives of Malaysian laws and Shariah. This paper examined doctrinal research by examining relevant legal provisions, Shariah rulings, fatwa, cases, and non-legal literature on estate administration. This paper concludes that there is a lacuna in the estate administration of cryptocurrency as its regulatory framework is still new and evolving. Therefore, the legal and Shariah issues highlighted in this paper may provide some important policy implications for regulators and policymakers to fulfil the lacuna in the estate administration of cryptocurrency in Malaysia.